Aşağıdaki denklemi çözün ...? 2 ^ (4x) - 5 (2 ^ (2x - 1/2)) + 2 = 0

Aşağıdaki denklemi çözün ...? 2 ^ (4x) - 5 (2 ^ (2x - 1/2)) + 2 = 0
Anonim

Cevap:

# X = İn ((25 + -sqrt (609)) / (2sqrt (2))) / (LN4) #

Açıklama:

2. ^ (4x) -5 (2 ^ (2x-1/2)) + 2 = 0 <=> #

2. ^ ((2x) ^ 2) -5 * 2 ^ (2x) renkli (kırmızı) ila (xx) 5 * 2 ^ (- 1/2) + 2 = 0 <=> #

# (2 ^ (2x)) ^ 2- (25 / sqrt (2)) 2 ^ (2x) + 2 = 0 <=> #

Şimdi ikinci dereceden denklemin görülmesi kolay olmalı.

Değiştirmek zorundasın 2. ^ (2x) # bir y ile

# <=> y ^ 2 (25 / (2)) y + 2 = 0 #

• y = (25 / sqrt (2) + - sqrt (625 / 2-2 * 2 * 2)) / 2 #

• y = (25 / sqrt (2) + - sqrt (609/2)) / 2 #

/ # 2 - # 2 ^ (2x) y = (sqrt (609/2), 25 / sqrt (2) *) =

Uygulama logaritmaları:

# 2xln2 = İn ((25 + -sqrt (609)) / (2sqrt (2))) #

# X = İn ((25 + -sqrt (609)) / (2sqrt (2))) / (2ln2) #

# X = İn ((25 + -sqrt (609)) / (2sqrt (2))) / (LN4) #